Covalent Organic Frameworks‐Based Membranes as Promising Modalities from Preparation to Separation Applications: An Overview. Issue 8 (31st May 2022) - Rasheed, Tahir; Khan, Sardaraz; Ahmad, Tauqir; Ullah, Nisar
Abstract: Covalent organic frameworks (COFs) are a promising class of porous crystalline materials made up of covalently connected and periodically protracted network topologies through organic linkers. The tailorability of organic linker and intrinsic structures endow COFs with a tunable porosity and structure, low density, facilely‐tailored functionality, and large surface area, attracting increasing amount of interests in variety of research areas of membrane separations. COF‐based membranes have spawned a slew of new research projects, ranging from fabrication methodologies to separation applications. Herein, we tried to emphasis the major developments in the synthetic approaches of COFs based membranes for a variety of separation applications such as, separation of gaseous mixtures, water treatment as well as separation of isomeric and chiral organic compounds. The proposed methods for fabricating COF‐based continuous membranes and columns for real world applications are also thoroughly explored. Finally, a viewpoint on the future directions and remaining challenges for COF research in the area of separation is provided. Abstract : Covalent Organic Frameworks are an emerging class of porous crystalline materials, having large surface area, high porosity, low density and systematically ordered pore structures. Furthermore, the facile functionalization of COFs makes them suitable candidates for a variety of membrane science based separation applications.